Drosophila Centrosomin Protein is Required for Male Meiosis and Assembly of the Flagellar Axoneme - Li, Kaijun (The Rockefeller University Press, 1998)
Centrosomes and microtubules play crucial roles during cell division and differentiation. Spermatogenesis is a useful system for studying centrosomal function since it involves both mitosis and meiosis, and also transformation of the centriole into the sperm basal body. Centrosomin is a protein localized to the mitotic centrosomes in Drosophila melanogaster. We have found a novel isoform of centrosomin expressed during spermatogenesis. Additionally, an anticentrosomin antibody labels both the mitotic and meiotic centrosomes as well as the basal body. Mutational analysis shows that centrosomin is required for spindle organization during meiosis and for organization of the sperm axoneme. These results suggest that centrosomin is a necessary component of the meiotic centrosomes and the spermatid basal body.